KORELASI KECEMASAN MATEMATIKA DAN KEMAMPUAN PESERTA DIDIK DALAM MENYELESAIKAN MASALAH MATEMATIKA SEKOLAH DASAR - Madyaning Ratri, Titis; Irianto , Dede Margo; Yuniarti, Yeni (Jurnal Ilmiah PENDAS: Primary Educational Journal, 2023)
Mathematics is an important element in human life, where almost every aspect of human life is related to problem related to mathematics. The existence of anxietyin participating in mathematical problems in everyday life. This study aims to analyze the relationship between math anxiety and student’ ability to solve problems and their causes at SDN 029 Cilengkrang, Bandung City. The research method used is a qualitative descriptive method with a case study approach. The subjects in this study were class 6A students at SDN 029 Cilengkrang Bandung City fir the 2022/2023 academic year. The results showed that there was a negative collelation between anxiety and students’ ability to solve math problems